Nonleisure-time physical activity as a protective factor against sarcopenia in hemodialysis patients: a prospective cohort study - Chang, Liyang; Zheng, Yujuan; Ding, Yan; Long, Zhiqiao; Zhang, Hongmei (Frontiers in Nutrition, 2025)
ObjectivesSarcopenia is prevalent among individuals undergoing maintenance hemodialysis (MHD) and is influenced by sedentary lifestyles. Although leisure-time physical activities have been shown to prevent sarcopenia in patients undergoing MHD, the impact of nonleisure-time physical activities on sarcopenia has not yet been examined in prospective studies.MethodsThis prospective cohort study, conducted in 2020 with a 12-month follow-up, included stable MHD patients without baseline sarcopenia. Sarcopenia was diagnosed according to the 2019 Asian Working Group for Sarcopenia criteria. Physical activity was assessed using the International Physical Activity Questionnaire. Additionally, demographic, dietary, nutritional, and laboratory data were collected. Modified Poisson regression analysis was employed to evaluate the impact of physical activity on the risk of developing sarcopenia.ResultsAmong the 196 MHD patients who completed the 1-year follow-up, 29 (14.8%) developed sarcopenia. The average total physical activity was 1,268 METs/week, with leisure-time activity averaging 300 METs/week and nonleisure-time activity averaging 724 METs/week. Adjusted analyses indicate that leisure-time physical activities do not significantly affect the risk of sarcopenia (RR = 0.920, 95% CI = 0.477–1.951; P > 0.05), whereas nonleisure-time physical activities are significantly associated with a reduced risk of sarcopenia (RR = 0.449, 95% CI = 0.248–0.814).ConclusionActively participating in physical activities (nonleisure-time physical activities) can reduce the incidence of sarcopenia in patients undergoing MHD. Promoting such activities may be an effective strategy to enhance physical fitness and mitigate sarcopenia risk among this population.